Derivative-Free Optimization of Offshore Production Platforms Sharing a Subsea Gas Network ⁎. Issue 8 (2018) - Camponogara, Eduardo; Machado, Amanda S.; Silva, Thiago L.; Giuliani, Caio M.; Vieira, Bruno F.; Teixeira, Alex F.
Abstract: Several systems in the real-world arise from the integration of subsystems, bringing about the need for coordination to share limited resources and drive economic gains. Large offshore oilfields fall in this category, such as the Santos Basin, which consists of multiple reservoirs that are operated by platforms interconnected by a subsea gas network. The high content of CO2 imposes constraints on the produced gas delivered to an onshore terminal. To cope with complexity, previous works proposed modeling the production platforms in terms of boundary conditions, thereby decoupling the platform local problems from the optimization of integrated operations. This work follows the same strategy, however proposes the use of derivative-free optimization to find boundary conditions that optimize the overall production. Such an approach adds flexibility from the direct use of simulators for the gas network, while allowing the platform problems to be solved with the method of choice, possibly using mixed-integer nonlinear or linear optimization. The derivative-free approach was shown to be effective in the optimization of the integrated production of the Santos Basin.